Optimization in Chemical Modification of Single-Stranded siRNA Encapsulated by Neutral Cytidinyl/Cationic Lipids - Li, Zheng; Wang, Xixian; Zhou, Xinyang; Wang, Jie; Guan, Zhu; Yang, Zhenjun (Frontiers in Chemistry, 2022)
Single-stranded siRNA (ss-siRNA) refers to the antisense strand of siRNA which plays the role of gene silencing. Since the stability of single-stranded RNA is worse, we employed a homemade neutral cytidinyl/cationic lipids delivery system and chemical modifications to improve its stability and activity. The results showed that with the aid of mixed lipids, unmodified ss-siRNA could knock down 40% of target mRNA at 25 nM. Optimization with fully 2ʹ-F/2ʹ-OMe, phosphorothioate (PS), or 5ʹ-terminal phosphorylation, most of ss-siRNA could knock down 80% of target mRNA at 25 nM. Continuous application of this strategy, could still result potent ss-siRNA (79%). Further mechanism investigation by knocking down AGO2, the ss-siRNAs couldn’t effectively silence target genes. Biodistribution study in vivo showed that ss-siRNA was less durable than siRNA, but spread more quickly to tissues. Taken together, a safe and efficient ss-siRNA delivery and modification strategy has been provided, which lays the foundation of future works.